2010
DOI: 10.1063/1.3432736
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, structural, and magnetic effects of 3d transition metals in hematite

Abstract: We present a density-functional theory study on the electronic structure of pure and 3d transition metal ͑TM͒ ͑Sc, Ti, Cr, Mn, and Ni͒ incorporated ␣-Fe 2 O 3. We find that the incorporation of 3d TMs in ␣-Fe 2 O 3 has two main effects such as: ͑1͒ the valence and conduction band edges are modified. In particular, the incorporation of Ti provides electron carriers and reduces the electron effective mass, which will improve the electrical conductivity of ␣-Fe 2 O 3. ͑2͒ The unit cell volume changes systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
104
3
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 31 publications
(28 reference statements)
15
104
3
2
Order By: Relevance
“…[89][90][91] We therefore, assign the Raman peak at 658 cm -1 to distortioninduced Raman mode activated upon doping. This is consistent with the changes in cell parameters (unit cell contraction) observed by Zhao et al, 67 Huda et al, 82 doping. Doubling the Ti concentration (cyan, 6% Ti) did not change the intensity of the peak while doubling the film thickness (dark blue, 40 nm) resulted in enhanced peak intensity.…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptsupporting
confidence: 92%
See 1 more Smart Citation
“…[89][90][91] We therefore, assign the Raman peak at 658 cm -1 to distortioninduced Raman mode activated upon doping. This is consistent with the changes in cell parameters (unit cell contraction) observed by Zhao et al, 67 Huda et al, 82 doping. Doubling the Ti concentration (cyan, 6% Ti) did not change the intensity of the peak while doubling the film thickness (dark blue, 40 nm) resulted in enhanced peak intensity.…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptsupporting
confidence: 92%
“…It was found that Ti incorporation is associated with a reduction in the unit cell volume and reduced Fe−Fe bond length, which could affect the hopping probability of charge carriers, consistent with the observation by Zhao et al 82 Local distortion was also observed but not discussed as an effective factor. Changes in the unit cell volume and in general changes in the local symmetry is particularly important since the charge transport in hematite is limited by small polaron hopping.…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptsupporting
confidence: 78%
“…Considering the strong spin polarization effect for magnetic system, studies [19,20,41] orbital and Fe 3d orbital, respectively, corresponding to the experimental investigation well [42], and the Fe 3d orbital overlap with O 2p orbital between -8.5 eV to -6.0 eV and -6.0 eV to 0 eV, between 1.5 eV to 3.5 eV orbital hybridization happens again, consistent to the previous results [43]. Comparisons of the present values with the results of previous experiments [44][45][46][47][48] and calculations [49] are listed in Table 1.…”
Section: Surface Modelssupporting
confidence: 85%
“…Hematite is isostructural with corundum (α-Al 2 O 3 ) and cromia (α-Cr 2 O 3 ), which have been studied extensively, both by means of atomistic simulation techniques and experimentally [53][54][55][56][57]63,[124][125][126]. The hematite structure contains iron and oxygen atoms arranged in a trigonal-hexagonal scalenohedral (class) structure with space group R-3c and lattice parameters a = b = 5.0356 Å, c = 13.7489 Å, with six formula units per unit cell [1].…”
Section: Bulk α-Fe 2 O 3 Structurementioning
confidence: 99%
“…The interactions of various molecular species with iron (hydr)oxide surfaces have also been extensively investigated. The magnetic and electronic structure of α-Fe 2 O 3 has been studied via the Density Functional Theory methods [53][54][55][56][57], whereas similar calculations of point defects (e.g., interstitials, vacancies and substitutional dopants) in hematite have shown these to have profound effects on the electronic properties [57][58][59][60]. Trainor et al [61] and Wang et al [62] have computed various possible structures of the hematite (0001) surface using spin-density functional theory, whereas, de Leeuw and Cooper have employed classical interatomic potential calculations to simulate the hydrated surface structures of white rust [Fe(OH) 2 ], goethite (FeOOH) and hematite (α-Fe 2 O 3 ) [63].…”
Section: Introductionmentioning
confidence: 99%